Pengaruh Pengetahuan Perpajakan dan Lingkungan terhadap Kepatuhan WPOP KPP Pratama Medan Timur - Br Hutagalung, Camelya Adelyani; Dison Silalahi, Alistraja; Wardany, Sri; Wirananda, Henny Andriyani (UNIVERSITAS DHARMAWANGSA, 2025)
This study aims to determine and analyze the influence of tax and environmental knowledge on individual taxpayer compliance registered at the East Medan Pratama Tax Office (KPP Pratama). This study used a quantitative approach. The sample size was 100 individual taxpayers at the East Medan Pratama Tax Office. The data source used in this study was primary data. The data collection technique used a questionnaire. The data were analyzed using multiple linear regression with the help of SPSS version 25. The results show that tax knowledge has a positive and significant effect on taxpayer compliance. The environment also has a positive and significant effect on taxpayer compliance. Simultaneously, tax and environmental knowledge significantly influenced individual taxpayer compliance, contributing 50.4%. This study concludes that increasing tax knowledge and a supportive environment are crucial to encouraging individual taxpayer compliance. Therefore, it is recommended that the tax authorities strengthen education and outreach programs and encourage the role of the environment in fostering a culture of tax compliance.